Milk Donation Awareness of Parents, Health Workers and Lactation Consultants: Survey Findings - Olga L. Lukoyanova; Tatyana E. Borovik; Irina A. Belyaeva; Leyla S. Namazova-Baranova; Galina V. Yatsyk; Elena V. Shepkina; Ulyana M. Lebedeva; Vladimir I. Phurtsev; Yakov Ya. Yakovlev; Lyudmila N. Sophronova; Liliana A. Dautova; Olga V. Nodvikova; et al. (Вопросы современной педиатрии, 2016)
Background. Today, in Russia there is no practice of using donor milk in hospitals, while abroad it is a common technique of caring for premature and low-weight infants.Objective: Our aim was to study the milk donation awareness of parents of children under the age of 1, health workers and lactation consultants.Methods. A sample survey was carried out.Results. The study involved 2,332 respondents from 13 medical institutions in 11 cities and towns located in 6 federal districts of the Russian Federation, including 1,134 mothers, 413 fathers, 692 health workers, and 93 lactation consultants. 1,007 (65.1%) parents (mothers and fathers) and 541 (68.9%) specialists (health workers and lactation consultants) believe that feeding of a sick newborn with donor milk is useful in the absence of breast milk. Only 609 (39.4%) parents and 363 (46.2%) professionals would agree to use donor milk for their children in the absence or lack of mother’s milk. Only 1/3 of the respondents — 560 (36.2%) parents and 259 (33.0%) professionals — believe that donor milk is safe. 565 (36.5%) parents and 475 (60.5%) professionals have heard something about breast milk banks and 1,013 (65.5%) parents and 449 (57.2%) professionals believe that the establishment of such banks is reasonable. Most of the mothers (830; 73.2%) involved in the study would agree to become breast milk donors, and 219 (53%) fathers would approve their wives’ decision to become donors.Conclusion. The study has revealed low respondents’ awareness of the use and safety of donor milk. However, most of the mothers are willing to become breast milk donors. More than half of the parents and professionals involved in the study believe that it is reasonable to create milk banks.